GranDIHC-BR 2025-2035 – GC3: Plurality and Decoloniality in HCI - de Oliveira, Leander Cordeiro; Amaral, Marília Abrahão; Bim, Silvia Amélia; Valença, George; Almeida, Leonelo Dell Anhol; Salgado, Luciana Cardoso de Castro; Gasparini, Isabela; da Silva, Claudia Bordin Rodrigues (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Discussions about the relationship between technologies in social contexts have been present in the Brazilian Human-Computer Interaction (HCI) community for years, including in the “Grand Challenges of Research in Human-Computer Interaction in Brazil” from 2012-2022. The challenge presented here seeks to continue these discussions, including and expanding through Plurality, the intersections between diversity, equity, accessibility, and inclusion. This challenge also proposes a critical analysis of the methods and theories used in HCI research and productions, seeking a decolonial perspective of scientific and technological processes in our Brazilian and Latin American territorial reality, which often originated in the global north and replicated in other regions. Besides geographical positions, it also considers how body and identity can generate exclusion or inclusion. We also discuss that the decoloniality process corroborates plurality and thus influences the creation of our theories, methodologies, actions, practices, technologies, interactive computational systems, and, consequently, the people who use them.